The Relationship Between Burnout and Workload Among Nurses in the Malaqbi 2 and Malaqbi 3 Inpatient Wards at the Provincial General Hospital of West Sulawesi - Suryadi; Thahirah; Pantandean, Dewarawati; Armidayanti; Sanidra, Aliyah; Duka, Ahmad Suhardi (Ammar Dharma Foundation, 2026)
Background: Nurses working in inpatient wards are required to deliver continuous and comprehensive nursing care. This condition often results in a high workload, which is frequently associated with an increased risk of burnout. Burnout among nurses can negatively affect their well-being, job performance, and the quality of patient care, making it an important occupational health issue in hospital settings.Objective: This study aimed to analyze the relationship between workload and burnout among nurses working in the Malaqbi 2 and Malaqbi 3 inpatient wards at the Provincial General Hospital of West Sulawesi.Methods: A cross-sectional study design was employed, involving 46 nurses selected using a total sampling technique. Data were collected using a structured questionnaire consisting of a workload measurement instrument and a burnout instrument adapted from the Maslach Burnout Inventory. Data analysis included univariate analysis to describe respondent characteristics and variable distributions, and bivariate analysis using the Spearman correlation test to examine the relationship between workload and burnout.Results: The findings revealed that the majority of nurses experienced a heavy workload, while most respondents reported mild levels of burnout. Statistical analysis showed no significant relationship between workload and burnout (p = 0.200), although a weak positive correlation was identified between the two variables.Conclusion: The study indicates that nurse burnout is not solely influenced by workload but is also affected by other factors, including individual characteristics, work environment, and organizational support. Hospital management is therefore encouraged to implement comprehensive strategies focusing on workload management, psychological support, and improvement of the work environment to prevent burnout and enhance nurses’ well-being and quality of care.